Remuneration and Management Behavior Evaluation: A Critical Review - Yuliarini, Sarah; Ismail, Ku Nor Izah Ku (Archives of Business Research, 2016)
Environmental accounting (EA) practices are developing rapidly in some countries and has a positive impact on their organizations. Sustainability report (SR), as an indicator of EA practices, helps company in improving its reputation, set by the management. However, some countries in ASEAN including Indonesia do not have relevant accounting standards on the environment. EA practice is still not widely known in Indonesia, although, internationally there have been standards that provide guidelines on environmental practices such as the Global Reporting Initiative (GRI). Another prospect in GRI is remuneration. Remuneration is a part of personnel cost which is a motivation about the positive effects of EA practices to disclose management concerns. This a critical review on evaluation of remuneration structure and the consistency of EA practices in the Sustainability Report .